2020
DOI: 10.1007/s40119-020-00161-y
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Invasive and Echocardiographic Transvalvular Gradients after Transcatheter Aortic Valve Replacement

Abstract: Introduction: Lower transcatheter aortic valve replacement (TAVR) pressure gradients have been reported after implantation of self-expanding valves compared with balloon-expandable valves; however, there is a paucity of data on the relationship between invasively measured transvalvular pressure gradients and Doppler-derived measurements. Methods: From September 2013 to September 2018, patients with native aortic valve stenosis who had both intraoperative invasive and postoperative echocardiography transvalvula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Furthermore, the discordance of trans-valvular gradients between Doppler-derived measurements and invasive measurements is described among different type of THV. Aalaei-Andabili et al 6) have demonstrated a significant difference between invasive measurement and Doppler-derived gradients (7.5±3 mmHg vs. 11.4±4.5 mmHg, p<0.001) after BE-THV implantation. In contrast, there was no significant difference by either measurement for SE-THV (invasive vs. Doppler-derived gradient: 10.3±3.4 mmHg vs. 8.5±4.6 mmHg, p=0.18).…”
mentioning
confidence: 94%
“…Furthermore, the discordance of trans-valvular gradients between Doppler-derived measurements and invasive measurements is described among different type of THV. Aalaei-Andabili et al 6) have demonstrated a significant difference between invasive measurement and Doppler-derived gradients (7.5±3 mmHg vs. 11.4±4.5 mmHg, p<0.001) after BE-THV implantation. In contrast, there was no significant difference by either measurement for SE-THV (invasive vs. Doppler-derived gradient: 10.3±3.4 mmHg vs. 8.5±4.6 mmHg, p=0.18).…”
mentioning
confidence: 94%
“…Prior data have shown that Doppler-measured and invasive, directly measured gradients can significantly vary [3][4][5][6]. Pressure recovery phenomena and fluid hemodynamics have been implicated as explanations.…”
mentioning
confidence: 99%